ESTABLISHMENT AND AUTHENTICATION OF A UV SPECTROPHOTOMETRIC APPROACH FOR MEASURING EMBELIN CONTENT IN BULK AND FORMULATED SAMPLE - Kritika R. Saboo; Rohit R. Ghadge
A UV-spectrophotometric method for the estimation of embelin isolated from Embelia ribes berries as per ICH guidelines Q2 (R1) was developed. It is simple, quick, accurate, and affordable. The wavelength of embelin was found to be 294.3 nm; and was linear in the concentration range 2-12 (So(Bg mL-1 with 0.997 correlation coefficient. The method was applied to pharmaceutical formulation and the drug estimated was found to be 97.99 % and was in good agreement with the label claim. The accuracy of the method was performed at three different levels, between 80 to 120 %; with % recovery obtained 98.54 - 99.98 %. The low values of % RSD indicate that the method is accurate and reproducible. Interday, intraday variations, and repeatability were studied as precision parameters. A lower % RSD value than 2 indicates the developed method is precise. Ruggedness of the proposed method was studied with the aid of two analysts.s